Penerimaan Karyawan Baru Menggunakan Metode Profile Matching - Joko (Jurnal PROCESSOR, 2020)
Company or agencies can run and grown up with the labor or employees who have the ability in accordance with the need a clue who these company or agencies. In this case the recruitment process for employees can be transferred to various criteria and the ability of indispensable. The selection process used to assess the relative servant candidates so that the capabilities of quality or the number of civil servants. To overcome these issues researchers conducted the design and manufacture of systems of supporting the decision the reception of new employees. .Methods used in the research uses a method of profile macthing. The program designed by the profile matching and design system The assessment by using the method profile matching produce information rangking of final score.. The decision support system for a new entry that would be an alternative for agencies to help ease in the decision-making process and provide solutions to problems. The evaluation process also more quickly and given free to users to vote for employees who will be assessed.